2023
DOI: 10.3389/fnagi.2023.1117250
|View full text |Cite
|
Sign up to set email alerts
|

A study of auxiliary screening for Alzheimer’s disease based on handwriting characteristics

Abstract: Background and objectivesAlzheimer’s disease (AD) has an insidious onset, the early stages are easily overlooked, and there are no reliable, rapid, and inexpensive ancillary detection methods. This study analyzes the differences in handwriting kinematic characteristics between AD patients and normal elderly people to model handwriting characteristics. The aim is to investigate whether handwriting analysis has a promising future in AD auxiliary screening or even auxiliary diagnosis and to provide a basis for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…During non-alphabetical and alphabetical writing, Alzheimer's disease patients showed less automated movements, decreased writing velocity and decreased frequency of up-and-down strokes [98]. Tremendous writing pressure and poorer writing stability were also found in patients with Alzheimer's disease [99]. Compared with regular writing and multiply repeated single-letter writing, an all-capital-letters writing task was better for distinguishing MCI patients from healthy controls [100].…”
Section: Performing Cognitive Screening Before MCImentioning
confidence: 99%
“…During non-alphabetical and alphabetical writing, Alzheimer's disease patients showed less automated movements, decreased writing velocity and decreased frequency of up-and-down strokes [98]. Tremendous writing pressure and poorer writing stability were also found in patients with Alzheimer's disease [99]. Compared with regular writing and multiply repeated single-letter writing, an all-capital-letters writing task was better for distinguishing MCI patients from healthy controls [100].…”
Section: Performing Cognitive Screening Before MCImentioning
confidence: 99%
“…Some researchers also used the same digital pen described in the following sections of this paper to extract highly generalized handwriting features through secondary extraction of the original handwriting information. Their experiments revealed that further processing of the raw data can improve classification performance [8,9].…”
Section: Introductionmentioning
confidence: 99%